2010
DOI: 10.1152/ajpendo.00263.2010
|View full text |Cite|
|
Sign up to set email alerts
|

Glucagon and lipid interactions in the regulation of hepatic AMPK signaling and expression of PPARα and FGF21 transcripts in vivo

Abstract: Hepatic glucagon action increases in response to accelerated metabolic demands and is associated with increased whole body substrate availability, including circulating lipids. The hypothesis that increases in hepatic glucagon action stimulate AMP-activated protein kinase (AMPK) signaling and peroxisome proliferator-activated receptor-α (PPARα) and fibroblast growth factor 21 (FGF21) expression in a manner modulated by fatty acids was tested in vivo. Wild-type (gcgr(+/+)) and glucagon receptor-null (gcgr(-/-))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 50 publications
10
74
0
Order By: Relevance
“…Our finding is consistent with Heiker et al (16), who showed that increased serum adiponectin results in an increase in AMPK activation via ADRs. Our results are also consistent with glucagon-mediated activation of AMPK in the liver (4,28). We demonstrated that fasting glucagon had a tendency to be decreased in the HFDϩPL compared with the HFDϩRIM group, which is cosnsistent with the results obtained for AMPK activation.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding is consistent with Heiker et al (16), who showed that increased serum adiponectin results in an increase in AMPK activation via ADRs. Our results are also consistent with glucagon-mediated activation of AMPK in the liver (4,28). We demonstrated that fasting glucagon had a tendency to be decreased in the HFDϩPL compared with the HFDϩRIM group, which is cosnsistent with the results obtained for AMPK activation.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been shown that glucagon modulates Fgf-21 expression [12][13][14][15]. Here, we extend these observations by reporting for the first time that glucagon increases, independently of endogenous insulin levels, circulating levels of FGF-21 in humans and rodents.…”
Section: Discussionsupporting
confidence: 78%
“…* p <0.05, ** p <0.01 and *** p <0.001 vs vehicle-treated groups (indicated as -). Each experiment was repeated three times The increase of FGF-21 plasma concentration by exogenous glucagon regardless of endogenous insulin production is somehow intriguing, in view of the contradictory results of earlier studies showing that insulin regulates FGF-21 [12,15,17,30]. Exogenous insulin increased plasma FGF-21 and Fgf-21 mRNA expression in skeletal muscle in humans [30].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations